Testing Carbohydrate Substance as Flash Based Flipbook Learning Media - Fadhila, Nida Ulfia Husna; Sulistiyawati , Sulistiyawati (Proceeding International Conference on Science and Engineering, 2019)
This study aims to produce a flash-based flipbook and find out the quality of flash-based flipbook products that are suitable for use as supporting learning media. The study consisted of preliminary research in the form of carbohydrate test practicum consisting of barfoed test, benedict test and iod / lugol test. The results of the study were developed into flash-based flipbook using macromedia flash and microsoft word 2010 through the data entry stage to the developer software, preparation of layouts and provision of activities on flash-based flipbook. The final product in the form of flipbook is flash-based. Flash-based flipbook was assessed by 1 material expert, 1 media expert, 1 science teacher, 3 peer reviewers, and tested on 10 junior high school students. The results of the evaluation of flashbased flipbook according to material experts were 90.87% (Very good), media experts 88.10% (Very good), peer reviewers 93.39% (Very good), biology teachers 75.00% (Good) , and 85.6% (Very good) student response. Based on this assessment, the flash-based flipbook that was developed is worthy of being used as a source of learning biology.